1995
DOI: 10.1103/physrevd.52.1920
|View full text |Cite
|
Sign up to set email alerts
|

Oscillons: Resonant configurations during bubble collapse

Abstract: Oscillons are localized, nonsingular, time-dependent, spherically symmetric solutions of nonlinear scalar field theories which, although unstable, are extremely long lived. We show that they naturally appear during the collapse of subcritical bubbles in models with symmetric and asymmetric doublewell potentials. By a combination of analytical and numerical work we explain several of their properties, including the conditions for their existence, their longevity, and their final demise. We discuss several conte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
375
2
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 322 publications
(392 citation statements)
references
References 30 publications
11
375
2
4
Order By: Relevance
“…where r is the distance to the center of an oscillon r = (x 2 1 +x 2 2 ) 1/2 and the width of the distribution was set to be r 0 ≃ 2.9 (in units of ( √ λ v) −1 ), suggested an optimal choice for a long living oscillon in [10]. Earlier studies have established the sensitivity both to the spatial size r 0 and the amplitude of the deviation from vacuum.…”
Section: Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…where r is the distance to the center of an oscillon r = (x 2 1 +x 2 2 ) 1/2 and the width of the distribution was set to be r 0 ≃ 2.9 (in units of ( √ λ v) −1 ), suggested an optimal choice for a long living oscillon in [10]. Earlier studies have established the sensitivity both to the spatial size r 0 and the amplitude of the deviation from vacuum.…”
Section: Propertiesmentioning
confidence: 99%
“…In higher dimensions, the long life time of certain oscillations was pointed out 30 years ago in [7,8] and then re-discovered [9] when the dynamics of first order phase transitions and bubble nucleation was studied. More extended investigations were carried out in [10], where conditions, like the size of the initial bubble, for long living oscillations were examined. In [8] oscillating objects were called pulsons, we adopt hereafter the definition oscillon according to [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, if we depart weakly from the sine-Gordon model, we expect long-lived "breather-like" states that can transition to both widely separated kink-antikink pair and also to particles. Such long-lived states have been discovered in various systems and have been termed "bions" in certain contexts and "oscillons" in others [9,10,11,12,13,14,15,16,17,18,19,20,21].…”
mentioning
confidence: 99%
“…When the gravity is turned off, there is localized, longevity, nonsingular solutions, which are called "oscillons", in this theory. On flat space, the oscillons have been studied by Bogolyubsky et al [1], and Copeland et al [2]. They found that the oscillons can be formed after a bubble collapses.…”
Section: Introductionmentioning
confidence: 94%